Pengaruh Manajemen Nyeri: Imajinasi Terbimbing Terhadap Nyeri Kepala Pada Pasien Hipertensi - Putri, Prahardian; Agustin, Ismar; Muliyadi, Muliyadi; Azwaldi, Azwaldi; Saputra, Reynaldi (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Hypertension is a condition when the systolic pressure exceeds 140 mmHg and the diastolic pressure exceeds 90 mmHg. A common symptom is headache. To overcome headaches, nursing implementation is carried out in hypertension patients. Methods: This type of writing is descriptive in the form of a case study. The approach used is the nursing implementation approach. This research was conducted to compare two respondents who had been given implementation. Results: The results of the study in both patients after the implementation of the pain study found that the pain scale in patient 1 was 7 and patient 2 was 6. After applying pain management and guided imagery, the pain scale changed to mild. In education about pain, after being given education, the two patients began to know about non-pharmacological pain management using guided imagery. Conclusion: Seeing the results of this case study, it is necessary to implement nursing to examine pain, provide a comfortable atmosphere, educate about the use of non-pharmacological of guided imagery to reduce headache pain